Targeting MTA1/HIF‐1α signaling by pterostilbene in combination with histone deacetylase inhibitor attenuates prostate cancer progression. (10th October 2017) - Butt, Nasir A.; Kumar, Avinash; Dhar, Swati; Rimando, Agnes M.; Akhtar, Israh; Hancock, John C.; Lage, Janice M.; Pound, Charles R.; Lewin, Jack R.; Gomez, Christian R.; Levenson, Anait S.
Abstract: The metastasis‐associated protein 1(MTA1)/histone deacetylase (HDAC) unit is a cancer progression‐related epigenetic regulator, which is overexpressed in hormone‐refractory and metastatic prostate cancer (PCa). In our previous studies, we found a significantly increased MTA1 expression in a prostate‐specific Pten ‐null mouse model. We also demonstrated that stilbenes, namely resveratrol and pterostilbene (Pter), affect MTA1/HDAC signaling, including deacetylation of tumor suppressors p53 and PTEN. In this study, we examined whether inhibition of MTA1/HDAC using combination of Pter and a clinically approved HDAC inhibitor, SAHA (suberoylanilide hydroxamic acid, vorinostat), which also downregulates MTA1, could block prostate tumor progression in vivo . We generated and utilized a luciferase reporter in a prostate‐specific Pten ‐null mouse model ( Pb‐Cre + ; Pten f/f ; Rosa26 Luc /+ ) to evaluate the anticancer efficacy of Pter/SAHA combinatorial approach. Our data showed that Pter sensitized tumor cells to SAHA treatment resulting in inhibiting tumor growth and additional decline of tumor progression. These effects were dependent on the reduction of MTA1‐associated proangiogenic factors HIF‐1 α, VEGF, and IL‐1 β leading to decreased angiogenesis. In addition, treatment of PCa cell lines in vitro with combined Pter and low dose SAHA resulted in more potent inhibition of MTA1/HIF‐1 α than by high dose SAHA alone. Our study provides preclinical evidence that Pter/SAHA combination treatment inhibits MTA1/HIF‐1 α tumor‐promoting signaling in PCa. The beneficial outcome of combinatorial strategy using a natural agent and an approved drug for higher efficacy and less toxicity supports further development of MTA1‐targeted therapies in PCa. Abstract : Utilization of dietary bioactive molecules as chemo‐sensitizers is an emerging approach in developing combination strategies that can potentially provide more efficacy and less toxicity for anticancer treatments. Our study offers preclinical proof for combinatorial strategy using natural product, pterostilbene, with histone deacetylase inhibitor, SAHA, as a MTA1‐targeted interventional therapy to abrogate prostate cancer. Changes in MTA1‐associated proangiogenic factors in serum may be used as molecular response biomarkers for such therapy.